Community interventions to prevent violence against women and girls in informal settlements in Mumbai: the SNEHA-TARA pragmatic cluster randomised controlled trial - Nayreen Daruwalla; Unnati Machchhar; Shanti Pantvaidya; Vanessa D’Souza; Lu Gram; Andrew Copas; David Osrin (Trials, 2019)
Abstract Background In a cluster randomised controlled trial in Mumbai slums, we will test the effects on the prevalence of violence against women and girls of community mobilisation through groups and individual volunteers. One in three women in India has survived physical or sexual violence, making it a major public health burden. Reviews recommend community mobilisation to address violence, but trial evidence is limited. Methods Guided by a theory of change, we will compare 24 areas receiving support services, community group, and volunteer activities with 24 areas receiving support services only. These community mobilisation activities will be evaluated through a follow-up survey after 3 years. Primary outcomes will be prevalence in the preceding year of physical or sexual domestic violence, and prevalence of emotional or economic domestic violence, control, or neglect against women 15–49 years old. Secondary outcomes will describe disclosure of violence to support services, community tolerance of violence against women and girls, prevalence of non-partner sexual violence, and mental health and wellbeing. Intermediate theory-based outcomes will include bystander intervention, identification of and support for survivors of violence, changes described in programme participants, and changes in communities. Discussion Systematic reviews of interventions to prevent violence against women and girls suggest that community mobilisation is a promising population-based intervention. Already implemented in other areas, our intervention has been developed over 16 years of programmatic experience and 2 years of formative research. Backed by public engagement and advocacy, our vision is of a replicable community-led intervention to address the public health burden of violence against women and girls. Trial registration Controlled Trials Registry of India, CTRI/2018/02/012047. Registered on 21 February 2018. ISRCTN, ISRCTN84502355. Registered on 22 February 2018.